The alterations of personal self-perception in the bibliodrama group - MARKEVIČIUS, GIEDRIUS (Psichologija, 1997)
In the context of group psychotherapy, bibliodrama is a modern group method uniting exegesis, drama, and psychotherapy. It enables - based upon the hermeneutical recall principle of human experiences, identification techniques, and feedback from the process of interpersonal interaction - every participant to deepen his/her own reflection and correct his/her self-perception. In this research the theoretical principles of bibliodrama, based on the dynamics of the petsonality's self-perception (1-structure) described by C. R. Rogers, were set forth; the repertory grid method was presented and research based upon it was carried out. The task of this research, based upon the repertory grid method, was to analize the common regularities of self-perception dynamics in the bibliodrama group. For this purpose, students of Vilnius universities were examined (a total of 16 participants of 2 bibliodrama groups ). The research proved the hypothesis: the self-perception of participants of bibliodrama became more congruent, more realistic, and more integral. It was ascertained that the personality's fragmentary system of self-perception altered towards an articulated system. The alterations of personal self-perception noticed in the bibliodrama group continued after the group work as well.
Keywords: Self-perception; bibliodrama